2019
DOI: 10.1080/21645515.2019.1649555
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant effect of enterotoxigenic Escherichia coli (ETEC) double-mutant heat-labile toxin (dmLT) on systemic immunogenicity induced by the CFA/I/II/IV MEFA ETEC vaccine: Dose-related enhancement of antibody responses to seven ETEC adhesins (CFA/I, CS1-CS6)

Abstract: Double-mutant heat-labile toxin (dmLT, LT R192G/L211A) of enterotoxigenic Escherichia coli (ETEC) is an effective mucosal adjuvant. Recent studies have shown that dmLT also exhibits adjuvanticity for antigens administered parenterally. In this study, we subcutaneously (SC) immunized mice with the ETEC adhesin-based vaccine, CFA/I/II/IV MEFA (multiepitope fusion antigen), adjuvanted with dmLT and examined the impact of dmLT on antibody responses specific to the seven adhesins in the vaccine construction [CFA/I,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…These antibodies were shown to be functional in that they prevented the adherence of ETEC strains to Caco-2 cells in vitro ( Fig 5 ). The dmLT adjuvant used has been evaluated for its effect on immunogenicity in this context when used as a parenteral adjuvant with a MEFA/I/II/IV-based vaccine [ 41 ]. While anti-ST antibodies were not assayed directly in this study, they have been shown to be induced previously using a toxoid fusion-based approach in other model animals [ 21 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies were shown to be functional in that they prevented the adherence of ETEC strains to Caco-2 cells in vitro ( Fig 5 ). The dmLT adjuvant used has been evaluated for its effect on immunogenicity in this context when used as a parenteral adjuvant with a MEFA/I/II/IV-based vaccine [ 41 ]. While anti-ST antibodies were not assayed directly in this study, they have been shown to be induced previously using a toxoid fusion-based approach in other model animals [ 21 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CssBA antigen was found to be safe up to a dose of 45 ug (highest dose tested), and the serum and mucosal antibody responses to the antigen were significantly improved by the addition of dmLT, including increased levels of anti-CS6 α4β7 cells in the peripheral blood and anti-CS6 fecal antibody levels [ 65 , 66 ]. Multiple epitope fusion antigens (MEFA) utilize CFA/I as a platform to express the dominant epitopes of other CFAs in a single protein, along with non-toxic LTA-LTB and ST [ 67 , 68 ]. MEFA vaccines stimulate neutralizing antibodies against the selected virulence antigens and piglets immunized with the MEFA–K88ac vaccine remained healthy following challenge [ 69 , 70 ].…”
Section: Etec Componentmentioning
confidence: 99%
“…Multiple epitope fusion antigens (MEFA) utilize CFA/I as a platform to express the dominant epitopes of other CFAs in a single protein, along with non-toxic LTA-LTB and ST [ 67 , 68 ]. MEFA vaccines stimulate neutralizing antibodies against the selected virulence antigens and piglets immunized with the MEFA–K88ac vaccine remained healthy following challenge [ 69 , 70 ].…”
Section: Etec Componentmentioning
confidence: 99%
“…An alternative strategy to co-administration would be to conjugate or fuse these toxins to non-immunogenic antigens, allowing the binding of the B-subunit to intestinal epithelial cells, resulting in uptake and transport through the epithelium and improved immunogenicity. Examples of this strategy in the literature include fusion proteins, such as fimbriae-toxin multi-epitope fusion antigens (MEFA) [ 94 , 95 , 96 , 97 , 98 , 99 ]. Although these showed promising results in inducing protective immunity after i.m and s.c. administration in mice, the protective efficacy of this vaccination strategy still needs to be assessed after oral administration and challenge infection.…”
Section: Oral Vaccination Strategiesmentioning
confidence: 99%